Flowering seasonality drives taxonomic, functional, and phylogenetic diversity of hummingbirds along an altitudinal gradient in northwestern Mexico - Gabriel López-Segoviano; Laura E. Nuñez-Rosas; Maribel Arenas-Navarro; Guillermo Huerta-Ramos; María del Coro Arizmendi (PLoS ONE, 2025)
Floral resources in the mountains of northwestern Mexico are strongly seasonal. This influences latitudinal, local, and altitudinal migration patterns in hummingbird species, resulting in temporal changes in hummingbird community structure over the flowering period. In this study, we evaluated how the seasonality of floral resources and latitudinal migration of hummingbirds influenced taxonomic, phylogenetic, and functional diversity along an altitudinal gradient. We examined the functional and morphological space occupied by resident and migrant hummingbird species, as well as the species’ functional niches and the phylogenetic structure of species assemblages in three sites of northwestern Mexico. We recorded hummingbird and flower abundance using two transects with 15 point counts on each altitudinal gradient in the Sierra Madre Occidental. The transects spanned from tropical deciduous forest to pine-oak forest and the ecotone between them. We recorded 20 hummingbird species and 70 flowering plant species belonging to 30 families. We found that taxonomic, phylogenetic, and functional diversity were linked to the flower abundance. Seasonal latitudinal hummingbird migration was less important for functional diversity (since migratory species performed redundant functional roles) than taxonomic and phylogenetic diversity. Seasonal flowering along the altitudinal gradient drives various types of hummingbird movements (local, altitudinal, and latitudinal), which increases the number of hummingbird species fulfilling each functional role. Apparent phylogenetic clustering in the ecotone may be due to a convergence between temperate and tropical forest flora and the midpoint of hummingbirds’ altitudinal migrations. Our study highlights the temporal dynamism and strong influence of floral seasonality on the structure of hummingbird communities in the mountains of northwestern Mexico.